Clinical and epidemiological characteristics of leptospirosis in the Zaporizhzhya region - Anand, J. B. V.; Onishchenko, T.; Оніщенко, Тетяна Євгенівна (Запорізький державний медичний університет, 2019)
Leptospirosis, as a natural focal zooanthroponosis, remains an urgent epizootological, epidemiological and ecological problem, as evidenced by the wide spread of the disease in the world and Ukraine, with high morbidity and mortality. The purpose of our study – to analyzed the incidence of leptospirosis based on the materials of Zaporizhzhia Regional Clinical Infectious Disease Hospital of Zaporizhzhia Regional Council. This is a retrospective analysis of 40 case histories of patients with leptospirosis treated in Zaporozhye Infectious Regional Hospital in 1985 and 2005. Diagnosis was based on the results of clinical and laboratory studies. Among the patients, there were males (32,8%), aged between 30-63 years.
Keywords: тези доповідей